THE TRAGEDY OF THE ENCLOSURES: AN ECO-FEMINIST PERSPECTIVE OF THE SALE OF OXYGEN AND PROSTITUTION IN COSTA RICA - Isla, Ana (2006)
This paper develops the premise that capitalism and patriarchy, which understandconservation in terms of enclosure, use it as another instrument of colonization of the ThirdWorld, women’s work, and nature. This paper connects two aspects of this process: the firstis the enclosure of the forest for as an oxygen generator/carbon sink; and the second is theenclosure of women’s labour through prostitution. As biodiversity and women’s non-wagelabour comprise the support system that local communities use for survival, selling oxygenand prostitution have become a war on subsistence and, consequently, an expansion ofpoverty. The author concludes that Costa Rica’s debt crisis provides grounds forrestructuring accumulation in the industrial world by selling oxygen/carbon sink capacity asthe technological solution to environmental destruction, and provides grounds for repairingmasculine anxiety, or “masculation,” by selling its women’s and children’s bodies as a resultof the inequality crisis